FAKTOR AKADEMIK DAN NON AKADEMIK PERSEPSI MAHASISWA SERTA DOSEN TERHADAP PENYELESAIAN PENULISAN THESIS PARA MAHASISWA S2 PENDIDIKAN BAHASA INGGRIS PASCASARJANA UNNES - Rukmini, Dwi; Bharati, Dwi Anggani Linggar (Universitas Negeri Semarang, 2015)
The problems of this research are what is the average time spent for the S2 English Education Program students for finishing their thesis, what academic and non academic handicaps faced by the students to finish the thesis, what academic and non academic handicaps faced by the lecturers to supervise the students in finishing their thesis, How is to solve the problems in finishing the thesis. The design of the research is descriptive qualitative with the population English Education Program (EEP) students after finishing their thesis examinations and the lecturers as the advisors. The samples taken are thirty students and eight lecturers chosen randomly. The data were collected through two questionnaires namely for students dealing with the studentsâ identity, questions dealing with academic factors, questions dealing with non academic factors, questions addressed to the lecturers. The conclusions taken are as follows: the studentsâ academic competence reflected in thirty students is good; the scores for the subjects directly related to the thesis are good, though some are repeated with the commulative achievement index of 3,55. The scores for the thesis examinations are starting from AB to A or 80 above. However, there are still some problems in writing the thesis especially in grammar, diction, spelling, punctuation, cohesion, coherence, content, reference, format, numbering. The errors occurred in all chapters including in writing the abstract, acknowledgement, table of content, cover, and bibliography. Most students have the guidance book to write the thesis; the process to get the advisor decree takes one week; the meeting with the advisors is scheduled; the oral communication mode can be direct meeting through telephone and through sms. it always gets the response for an appointment from the advisors for consultation.The time period from one meeting to the other with the supervisor is one week.The advisor is helpful and in average they master the material proposed by the students. Mostly there is no contradictory opinion between the first and the second advisors.The references available in the English department library are helpful for the students to write the thesis but not in the central library of Unnes; The examiners of thesis donât demand much revision; the data collection and the document preparation needed is well done; at the beginning the students do not master the material but after reading a lot and being guided by the advisors they know better.3) most of the students have great motivation in finishing the thesis for financial reason; most of the students are tough and patient in writing the thesis for the fact that they can finish the revision quickly; some students have very limited skill of research that makes them to be guided much; most of the students have politeness in asking the consultation though some do not. There are still some students who are reluctant to read the original books; they prefer to quote othersâ quotations and still make mistake in the format including in the numbering system.